3D Plasmonic Ensembles of Graphene Oxide and Nobel Metal Nanoparticles with Ultrahigh SERS Activity and Sensitivity. (17th May 2016) - Lin, Jing; Wang, Xiansong; Shen, Guangxia; Cui, Daxiang
Abstract : We describe a comparison study on 3D ensembles of graphene oxide (GO) and metal nanoparticles (silver nanoparticles (AgNPs), gold nanoparticles (GNPs), and gold nanorods (GNRs)) for surface-enhanced Raman scattering (SERS) application. For the first time, GNRs were successfully assembled on the surfaces of GO by means of electrostatic interactions without adding any surfactant. The SERS properties of GO/AgNPs, GO/GNPs, and GO/GNRs were compared using 2-mercaptopyridine (2-Mpy) as probing molecule. We found that GO/AgNPs and GO/GNPs substrates are not suitable for detecting 2-Mpy due to the very strong π - π stacking interaction between the 2-Mpy molecules and sp 2 carbon structure of GO. Conversely, the GO/GNRs substrates show ultrahigh SERS activity and sensitivity of 2-Mpy with the detection limit as low as ~10 - 1 5  M, which is ~2-3 orders of magnitude higher than that of the corresponding GNRs.